Pancreatico-colonic fistula after acute necrotizing pancreatitis. Diagnosis with spiral CT using rectal water soluble contrast media - (:unkn) unknown (My University, 2008)
CONTEXT: Colonic complications are rare but lethal events in acute pancreatitis. CASE REPORT: We report the case of a 42-year-old man who suffered from a pancreatico-colonic fistula following a necrosectomy for severe pancreatitis; the fistula was demonstrated by spiral computed tomography using rectal water soluble contrast media. CONCLUSION: Computed tomography with rectal contrast detects pancreatico-colonic fistulas.
Keywords: Adult; Humans; Male; Contrast Media; Colon; Rectum; Water; Solubility; Pancreas; Intestinal Fistula; Pancreatic Fistula; Pancreatitis, Acute Necrotizing; Tomography, Spiral Computed